The Effect of starter Cultures on the Portuguese Traditional Sausage "Paio do Alentejo" in Terms of its Sensory and Textural Characteristics and Polycyclic Aromatic Hydrocarbons Profile - Elias, M (2014)
“Paio do Alentejo” is a Portuguese dry-cured sausage, made with meat from the Alentejano pig breed. The main aim of this study is to evaluate the benefits of the use of starter cultures on the quality of the sausage, mainly with regard to its sensory properties, rheological characteristics and PAH profile. Three batches of the product were examined: S1-inoculated with a commercial starter comprising Lactobacillus spp., Micrococcaceae and yeasts; S2-inoculated with a starter comprising Lactobacillus sakei and Staphylococcus xylosus; C-the control batch, was not inoculated. A sensory panel of 12 experts analysed samples in accordance with a descriptive analysis using a structured scale. A Texture Profile Analysis and 16 EPA priority PAHs for dry fermented sausages were performed. Both inoculated batches were well received by the judges, no significant differences being noted between them. The use of S2 led to a slight improvement in terms of cohesiveness. However, the use of starter cultures was not found to influence PAH content.